ANALISIS ISU BUDAYA SPESIFIK YANG MENGANDUNG EKSPRESI BOOSTER DALAM TEKS TERJEMAHAN SERIAL YOUTUBE MALAM MINGGU MIKO - NFN Ilham (Kantor Bahasa Provinsi Gorontalo, 2020)
Nowadays, technology helps us to make life easier. However, the existence of technology sometimes causes significant problems such as subtitle automation on YouTube channels on booster expressions that help us to understand the meaning of Cultural Specific Items (CSI) or Specific Cultural Elements in the Malam Minggu Miko 2 series by Raditya Dika. The existence of the free translation feature raises the unclear expression of the booster, confusing the audience reading the target text. This research is a qualitative research method with a case study embedded in the Sunday Night episode Miko 2: Cosplay Sakura which has been watched by more than one million viewers. The results of this study indicate that booster expressions in the speech of characters in YouTube subtitles are influenced by aspects of multimodality, especially in transferring Specific Cultural Elements by looking at discourse in the text.